Stability Analysis and Monitoring Method for the Key Block Structure of the Basic Roof of Noncoal Pillar Mining with Automatically Formed Gob-Side Entry - Jianning Liu; Manchao He; Yajun Wang; Ruifeng Huang; Jun Yang; Xichun Tian; Can Ming; Shan Guo (Advances in Civil Engineering)
The key block of the basic roof is the main contributor to the structural stability of a roadway. Research on the stability of the key block structure is of great significance for the promotion of noncoal pillar mining with automatically formed gob-side entry (GEFANM) technology. This paper is set in the engineering context of the GEFANM experiment at the Ningtiaota Coal Mine. The study fully considered the differences in the gob roof caving on the roof-cutting-line side, and the range of rotation angles to maintain a stable key block was determined. Based on this range of rotation angles, the range of safe bulking coefficients of gangue was calculated. The bulking coefficient of the gangue on the gravel side of the roadway was used as the metric in a new monitoring method and in the calculation of the field parameters. The range of safe bulking coefficients was determined to be 1.40–1.37. Field monitoring was conducted to obtain the gangue bulking coefficient on the gravel side. Combining the roof and floor convergence data, when the bulking coefficient fell within the safe range, the convergence was 95–113 mm. In this stage, the key block structure was stable. When the gangue bulking coefficient fell outside the safe range, the convergence was larger, and cracks were observed. The key block may be vulnerable to instability. The results affirmed that the gangue bulking coefficient can be used as a monitoring metric to study the stability of key block structures.